2017
DOI: 10.1103/physrevlett.118.267202
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Griffiths Phase Inside the Ferromagnetic Phase of Ni1xVx

Abstract: Citation for published item:ngD uizhe nd qeretsdikD edne nd idEussisD r nd hroederD elmut nd ojtD homs nd fkerD eter tF nd rttD prnis vF nd flundellD tephen tF nd vnsterD om nd prnkeD ssel nd w¤ ollerD tohnnes F nd geD uthrine @PHIUA 9untum qri0ths phse inside the ferromgneti phse of xiIExxF9D hysil review lettersFD IIV @PTAF pF PTUPHPF Further information on publisher's website: Reprinted with permission from the American Physical Society: Physical Review Letters 118, 267202 c (2017) by the American Physical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 45 publications
8
39
0
Order By: Relevance
“…[8], and for recent experimental observations of GM singularities see Ref. [9]. In the quantum paramagnetic phase in the limit as T → 0 GM singularities are characterized by a dynamical exponent z ′ which varies as the QCP is approached.…”
mentioning
confidence: 98%
“…[8], and for recent experimental observations of GM singularities see Ref. [9]. In the quantum paramagnetic phase in the limit as T → 0 GM singularities are characterized by a dynamical exponent z ′ which varies as the QCP is approached.…”
mentioning
confidence: 98%
“…As a result, quenchedin chemical disorder between Mn and Fe leads to a continuum of atomic scale AFM-in-FM magnetic orderings over a broad composition interval. This unusual behavior is akin to a Griffiths [13][14][15][16] phase, and is responsible for the anomalous exchange hardening seen in this single-phase material.…”
Section: Introductionmentioning
confidence: 90%
“…Prior work [5,6] has shown that significant chemical disorder is present only on the (Mn,Fe) FCC sub-lattice, and that the moments on the Ru and Sn sites do not contribute meaningfully to the magnetic ordering. The relevant chemical and magnetic configurational degrees of freedom can therefore be restricted to the (Mn,Fe) FCC sub-lattice, while the Ru and Sn sub-lattices are present only during the electronic structure calculations used to generate training data to arXiv:1910.07543v1 [cond-mat.mtrl-sci] 16 Oct 2019 parameterize the chemomagnetic cluster expansion.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…This can promote what were weak essential singularities in thermodynamic quantities into power-laws. As a consequence, these quantum Griffiths-McCoy singularities [4,5] are important both for experiments [6] and numerical calculations [7][8][9]. For a more comprehensive discussion on Griffiths-McCoy singularities in a myriad of disordered models and on the role of disorder in general in quantum critical behavior, see [10].…”
Section: Introductionmentioning
confidence: 99%